2009
DOI: 10.1089/jwh.2009.1431
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Pregnancy Outcomes Associated with Extreme Weight Loss among Women with Hyperemesis Gravidarum

Abstract: Objective: To report the weight loss and associated symptoms experienced by a large cohort of women with hyperemesis gravidarum (HG). Methods: Data were obtained from an HG website registry, where women with HG were recruited on-line. Respondents were included if they experienced at least 1 live birth >27 weeks' gestation. Extreme weight loss was defined as a loss of >15% of prepregnancy weight. Results: Of the 819 women surveyed, 214 (26.1%) met criteria for extreme weight loss. These women were twice as like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 39 publications
(26 reference statements)
5
99
1
2
Order By: Relevance
“…According to the literature, HG is an important risk factor that causes dehydration and weight loss during pregnancy [5]. The study of Fejzo et al [20] indicated that 26.2 % of the women with HG suffered from severe weight loss ([%15) and another study of Fejzo et al [21] pointed out that nearly all of the recurrent HG cases (98.0 %) underwent weight loss in accordance with the findings of present study.…”
Section: Discussionsupporting
confidence: 88%
“…According to the literature, HG is an important risk factor that causes dehydration and weight loss during pregnancy [5]. The study of Fejzo et al [20] indicated that 26.2 % of the women with HG suffered from severe weight loss ([%15) and another study of Fejzo et al [21] pointed out that nearly all of the recurrent HG cases (98.0 %) underwent weight loss in accordance with the findings of present study.…”
Section: Discussionsupporting
confidence: 88%
“…Hyperemesis gravidarum (HG) is the most common cause of hospitalization in the first half of pregnancy and the second most common cause of antenatal hospitalization during pregnancy. Extreme weight loss is common among women with HG, suggesting that HG is a form of prolonged starvation in pregnancy and that the long-term effects of this condition on women and their offspring warrant further investigation (2). Measurement of maternal serum alpha fetoprotein (AFP), human chorionic gonadotropin (HCG), and unconjugated estriol (uE3) at the beginning of the second trimester of pregnancy is a well established screening test for trisomies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, specific iatrogenic adverse reactions (such as nausea, vomiting, constipation, and excessive weight gain) related to psychotropic treatment may further aggravate the classic clinical findings for pregnancy, thus indirectly facilitating the occurrence of both pregnancy complications and fetal and neonatal risks. Both prematurity and low birth weight have been reported in mothers who had suffered from intractable vomiting during pregnancy [52]. Vomiting in pregnancy may also lead to increased rates of maternal complications, such as gallbladder and liver dysfunction, renal failure, and retinal hemorrhage.…”
Section: Resultsmentioning
confidence: 99%
“…Vomiting in pregnancy may also lead to increased rates of maternal complications, such as gallbladder and liver dysfunction, renal failure, and retinal hemorrhage. For some women, this symptom, especially when due to hyperemesis gravidarum, may continue during postpartum and may be complicated by the onset of food aversions, muscle pain, nausea, and post-traumatic stress disorder-related features [52]. Excessive weight gain in pregnancy is associated with an increased risk of cardiac and pulmonary diseases, gestational hypertension and diabetes, thromboembolisms, obstructive sleep apnea, breast cancer, and fetal congenital abnormalities [53,54].…”
Section: Resultsmentioning
confidence: 99%